LOCATION BASED TRAVELLING GAME, Case Study: Historical Building at Semarang - Aji Nugroho, Robertus Setiawan; Prasetya, F.X. Dendra (PROXIES, 2012)
The awareness of user context is ultimate for a service-based system, as it could define what user needs tmd wlud should be prioritized based on the context itself. Understtuuling location, or more precisely position, provides a new perspective of how a system could help on givi:uag the best service thllt is needed by user. Tourist or travelers often want to know specific or thematic point 0/ interests such as historical building, culi1lll1Y places, unique landscapes or even lumnted places. This research aims to propose a new experience 0/ thematic traveling or tourism using location based game. Game could be a way of transfemng the knowledge and experiellCe in an interesting way. This research is aimed to deploy a generic framework of location based traveling game, so it can be implemented in different themes. But, as this reseorch is held in Semamng, which is /mown weU for the historical building around it, we will take this theme as cIISe study /01 the deployed system. Common mobile device with opensource pllltform (Android) will be used as the infrastructure for this Location Based Service. Keywords: LBS, Context-aware, TltlVeling Game, Service-Oriented